60.2k views
2 votes
Jenny solved the equation 1 – (2x + 4) = –4x + 5. Her work is shown. 1 − ( 2 x + 4 ) = − 4 x + 5 Line 1: 1 − 2 x + 4 = − 4 x + 5 Line 2: 5 − 2 x = − 4 x + 5 Line 3: 2 x = 0 Line 4: x = 0 What is the correct solution to the equation 1 – (2x + 4) = –4x + 5? Re-solve the equation to find the correct solution.

User Ecarrizo
by
4.9k points

1 Answer

2 votes

Answer:

4

Explanation:

Given the equation 1 – (2x + 4) = –4x + 5, we are to find the correct solution of the equation;

Step 1: Open the parenthesis;

1 – (2x + 4) = –4x + 5

1-2x-4 = -4x + 5

1-4-2x = -4x +5

-3-2x = -4x + 5

Step 2: Collect like terms

-2x + 4x = 5 + 3

2x = 8

Step 3: divide both sides by 2;

2x/2 = 8/2

x = 4

Hence the correct value of x is 4

User Felixs
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.